Pediatric pulmonary embolism and nephrotic syndrome - Costa,Raquel (2018)
Thromboembolic complications, such as pulmonary embolism, are well-documented complications in nephrotic syndrome. The authors report a case of a 10-year-old boy with nephrotic syndrome and history of thrombotic complications, who experienced a massive pulmonary embolism during nephrotic syndrome relapse. Clinical signs and symptoms were minimal; D-dimers were an important clue and computed tomography pulmonary angiography established the definitive diagnosis. Treatment with low weight heparin was effective. Screening for hereditary thrombophilia identified predisposition towards thrombosis. Although these events seem rare in children, the literature suggests that they are actually underdiagnosed. Clinicians should be aware of this clinical condition, in order to avoid delay or misdiagnosis and prevent a poor or fatal outcome.